Adult multifocal Langerhan's cell histiocytosis involving periodontal tissues - Vijay Kumar Chava; Vellampalli Udhaya Bhanu (Wolters Kluwer Medknow Publications, 2021)
Langerhans cell histiocytosis (LCH) is a rare inflammatory neoplasia characterized by uncontrolled stimulation and abnormal proliferation of Langerhans cells (LCs). It can present as unifocal or multifocal with local and systemic manifestations which involves various internal organs and mucosal tissues. The clinical course varies among individuals, ranges from spontaneous resolution to life-threatening conditions with multisystem involvement. Prognosis relies on the involvement of risk organs (liver, spleen, and bone marrow) at diagnosis, mainly on organ dysfunction, and response to initial therapy. The diagnosis is based on histological study of tissues samples and shows tissue infiltration with LCs and the tumor cells immunopositive for s100/CD1a/Langerin/CD68 focal). In the oral cavity, LCH affects the alveolar or cortical bone and causes ulcerated lesions involving various mucosal and periodontal tissues. This article reports a case of adult multifocal LCH involving periodontal tissues with 1½ year posttreatment follow-up showing regression of the lesion.